Alpha-asarone improves cognitive function of aged rats by alleviating neuronal excitotoxicity via GABAA receptors. (1st January 2020) - Chen, Yu; Gao, Xiaofeng; Liu, Qi; Zeng, Lili; Zhang, Kun; Mu, Keman; Zhang, Di; Zou, Huixi; Wu, Nan; Ou, Jierui; Wang, Qiantao; Mao, Shengjun
Abstract: Alzheimer's disease (AD), the most common form of dementia, still lacks effective treatment at present. Alpha-asarone (ASA) is the major compound isolated from the Chinese medicinal herb Acorus gramineus. It has been reported to enhance cognitive function in rodent models, yet its mechanism was not fully understood. In this work, we demonstrated that ASA improved the spatial memory, reduced the neuronal injury, and decreased the level of Aβ1-42 in the hippocampus of aged rats. The results also showed that ASA had the neuroprotective effects against glutamate toxicity and decreased cytoplasmic calcium level in primary hippocampal neurons. By comparing the multiple properties of ASA and propofol (PPF) via computer modelling, we speculated that ASA may bind to the PPF binding site of type A gamma (γ)-aminobutyric acid receptors (GABAA Rs). This was further supported by the whole-cell patch-clamp recording. Our results suggested that ASA, as a GABAA R positive allosteric modulator (PAM), can improve cognitive function of aged rats by alleviating the neuronal overexcitation. Furthermore, the binding mode of ASA on GABAA R may lay a foundation for structure-based drug design in AD therapy. Highlights: ASA improved spatial memory and reduced hippocampal Aβ1-42 in aged rats. ASA reduced glutamate toxicity and cytoplasmic calcium in hippocampal neurons. ASA worked as a PAM of GABAA R and alleviated neuronal hyperactivity. ASA would be a promising drug candidate in the treatment of AD. The binding mode of ASA on GABAA R lays a foundation for structure-based drug design.